Fertility Outcome and Safety of Ethiodized Poppy Seed Oil for Hysterosalpingography in 1,053 Infertile Patients: A Real-World Study - Li, Hongjiang; Ren, Yannan; Yan, Jianxiang; Huang, Meiling; Zheng, Bolin; Luo, Xiangmin; Huang, Suzhen; Cai, Siqing (Frontiers in Medicine, 2022)
Objective Ethiodized poppy seed oil for hysterosalpingography (HSG) is reported to display some therapeutic effect on infertility, but big a sample-size study under real clinical settings is still lacking to verify the speculation. Thus, this real-world study enrolled 1,053 infertile patients who underwent ethiodized poppy seed oil-based HSG to explore its fertility enhancement value. Method A total of 1,053 infertile patients who underwent HSG using ethiodized poppy seed oil as the contrast medium were retrospectively analyzed. The live birth rate and 3-, 6-, 12-month and total pregnancy rate were retrieved. Besides, adverse events during and after HSG were recorded. Results The 3-, 6-, 12-month and total pregnancy rate was 22, 36.8, 50, and 53.8%, respectively. The total live birth rate was 42.7%. Sub-group analyses showed that pregnancy rate was 53.7, 53.8, 54.1, and 62.4% in subgroups of primary infertility patients, secondary infertility patients, infertility patients with fallopian tube disease, and infertility patients with unknown cause, respectively. Meanwhile the live birth rate was 44.3, 41.3, 41.5, and 59.2% in these subgroups, separately. Multivariate logistic regression analysis disclosed that BMI ≥ 24 kg/m2, history of dysmenorrhea, and abnormity of sperm count or motility-related infertility were independently correlated with reduced pregnancy rate and livebirth rate (All Ps < 0.05). Adverse events mainly included pain (20.6%) and interstitial reflux (7.9%), which were mild and tolerable. Conclusion Ethiodized poppy seed oil for HSG discloses a satisfying fertility outcome with a tolerable safety profile in infertile patients; meanwhile, this effect might be influenced by BMI, history of dysmenorrhea, and paternal abnormity of sperm.